The Effect of the one minute paper strategy in the collection of General Methods of Teaching on the students of the Department of History in the College of Basic Education (Journal of the College of Basic Education, 2022)
The present study aimed at identifying the effect of the one-minute paper strategy in the collection of general methods of teaching methods among the students of History in the College of the Basic Education. The researcher used an experimental design with partial and post-test. The study sample consisted of (105) students (53) and (52) students for each group. Group (1) was chosen to represent the experimental group which were studying according to the one-minute strategy and group (2) Represent the control group that is taught in the normal manner. The two groups were rewarded in variables: (scientific background and level of intelligence). In order to achieve the objective of the research, a test was constructed consisting of (50) test paragraphs and verified the validity and stability of the test and its characteristics by appropriate statistical means. Using the t-test to process the data. The results showed that the students in the experimental group studied on the basis of one-minute paper on the students of the control group. In the light of the findings of the researcher developed a set of conclusions, recommendations and proposals